If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2y + -9) + -2y = 2(y + -2) + -5 Reorder the terms: 2(-9 + 2y) + -2y = 2(y + -2) + -5 (-9 * 2 + 2y * 2) + -2y = 2(y + -2) + -5 (-18 + 4y) + -2y = 2(y + -2) + -5 Combine like terms: 4y + -2y = 2y -18 + 2y = 2(y + -2) + -5 Reorder the terms: -18 + 2y = 2(-2 + y) + -5 -18 + 2y = (-2 * 2 + y * 2) + -5 -18 + 2y = (-4 + 2y) + -5 Reorder the terms: -18 + 2y = -4 + -5 + 2y Combine like terms: -4 + -5 = -9 -18 + 2y = -9 + 2y Add '-2y' to each side of the equation. -18 + 2y + -2y = -9 + 2y + -2y Combine like terms: 2y + -2y = 0 -18 + 0 = -9 + 2y + -2y -18 = -9 + 2y + -2y Combine like terms: 2y + -2y = 0 -18 = -9 + 0 -18 = -9 Solving -18 = -9 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| X+3=3x+14 | | 6n-2n+9=-3n+144-8n | | 2x*x=-6 | | 6n-n+9=-3n+144-8n | | 4w-6=16-7w | | 2(3z+4)-5=4z+7 | | n^2-2n-1=154 | | x^3+x^2-78=0 | | g(x)=6x-7 | | 2(4+n)-5forn=0 | | 5y+13=7y-2 | | -2r-3=6r+4 | | n^2-2n-1=38.5 | | (x/11)=(x/12)-14 | | n^2-2n-2=38.5 | | 6g-4(-6+3g)=1-g | | -5p+6+6p=11 | | -3/5-3/10 | | 8.4x+16.28=-11.6+16.04 | | 3-/5-3/10 | | x^2+8x+8=3x+4 | | 24+16x=75+17x | | (2z-3)(z+4)=(3z-2)(z+6) | | (-5p+8)=(7p-5) | | 4x+2=3(x-3)+5 | | 0=-5t+15 | | 7.6x-1.1=29.3 | | 2[3-(-8x-8)]=80x+86 | | 1.7+x=7.1 | | 2+1x=1 | | 2l+2(70)=600 | | 4/5x-8=9/5x |